When the remedy is worse than the disease: Risks of the administrative price control - Gonzáles Cucho, José Carlos (2020)
During the State of Emergency, the country has suffered from a shortage of certain essential products and services. To deal with this situation, the Legislative Branch and the Executive Branch have taken a series of measures. Price control is one of the alternatives that are usually proposed at the political and media level.This article analyses the types of administrative price control, its possibility of implementation in the Peruvian legal system and its effects on the market. Moreover, alternatives to the use of this instrument are proposed.